Tarqiyyah Ta’lim Kitāb al Jurumiyyah Bi Istikhdām al Thariqah al Dzihniyyah Ila Thullāb al Madrasah al Diniyyah Fi al Ma’had al Islām “ Dārul Falāh 5 Cukir Jombang - Anggun Kharisma; Isniyatun Niswah (Program Studi Pendidikan Bahasa Arab, 2024)
This research was conducted to find out how learning the book Aj Jurumiyyah uses the mind mapping method at Madrasah Diniah Darul Falah Lima Islamic boarding school. This research uses a qualitative approach. The descriptive qualitative approach aims to describe how to improve Arabic language learning using the mind map method. Data collection methods are observation, interviews, questionnaires. Data analysis methods, including the process of systematically researching and collecting data obtained from interviews, field observations, and documentation, as well as data validity methods, including credibility and use of reference materials. The results of the research are 1. learning the Book of Al-Jurumiyyah at Madrasah Diniah Darul Falah Lima Islamic Boarding School, namely by dividing the book into several parts or chapters. The discussion includes understanding the structure and organization of material in the context of learning Arabic grammar. This study highlights the importance of the Al-Jurumiyya Book in the Islamic boarding school curriculum in Indonesia, as the basis for Arabic grammar memorized by Salafi students. Traditional teaching methods and the challenges they face are also highlighted, including limited learning time and challenges for students graduating from state schools who are not yet familiar with grammar. 2. The use of the mind map method in learning the Al-Jurumiyyah Book at Madrasah Diniah Darul Falah Lima Islamic Boarding School aims to help students understand Arabic grammar concepts in a visual and structured manner. This method uses steps to organize information in mind maps to increase student participation and learning motivation. 3. The advantages include making it easier to understand the material in detail, increasing enthusiasm for learning, and clarifying the overall picture of Arabic grammar concepts. The obstacles encountered included the time needed to explain the material individually to students and the level of student involvement that was not yet optimal in the learning process.